PELAKSANAAN PENDIDIKAN KARAKTER BANGSA PADA PROGRAM STUDI ILMU KEPERAWATAN STIK BINA HUSADA PALEMBANG - Misnaini, Sari (Jurnal Pendidikan Guru, 2017)
Character education is a deliberate attempt to help people understand, care about and act according to ethical values. Since 2003 the character education is expected to be implemented by all educational units are integrated in classroom learning and school culture. Character education in schools need basic principles are easy to understand and be understood by students and each individual. In the implementation of character education includes three bases, that is class-based, culture-based and community-based campus. Ten characters are quite dominant implemented in STIK Bina Husada, namely religious, honest, discipline, tolerance, responsibility, creative, independent, caring social, democratic, and recognize excellence.